Randomisation, blinding and drug supply in interactive voice response trials - McEntegart, Damian (Henry Stewart Talks, 2018)
Interactive voice response systems (IVR) in clinical trials, Interactive web response systems (IWR), Randomization and medication management, Simple and stratified randomization techniques, Dynamic randomization techniques, Blinding and selection bias in clinical trials, Forced randomization, Open-label studies, Emergency code in clinical trials